Kesetaraan gender dalam praktik poligami: Tinjauan syariah dan hak asasi manusia di Indonesia - Al Faton, Hifzhul Miftah (Maliki Interdisciplinary Journal, 2024)
This research discusses the concept of gender equality and polygamy practices in Indonesia from a multidisciplinary approach. The concept of gender equality is examined from both socio-cultural and biological perspectives, depicting the differences between men and women and their roles in society. Additionally, the research also analyzes polygamy practices in Indonesia based on law, sharia, and human rights. The findings indicate the complexity in understanding and implementing gender equality, especially in the context of polygamy practices that remain a topic of debate in society.